Catalyst‐Controlled 1, 2‐ and 1, 1‐Arylboration of α‐Alkyl Alkenyl Arenes. (9th January 2019) - Bergmann, Allison M.; Dorn, Stanna K.; Smith, Kevin B.; Logan, Kaitlyn M.; Brown, M. Kevin
Abstract: Two methods are reported for the 1, 2‐ and 1, 1‐arylboration of α‐methyl vinyl arenes. In the case of 1, 2‐arylboration, the formation of a quaternary center occurred through a rare cross‐coupling reaction of a tertiary organometallic complex. 1, 1‐Arylboration was enabled by catalyst optimization and occurred through a β‐hydride elimination/reinsertion cascade. Enantioselective variants of both processes are presented as well as mechanistic investigations. Abstract : Möglichkeiten offenhalten : Syntheseverfahren für die 1, 2‐ und 1, 1‐Arylborierung von α‐Alkylalkenylarenen wurden entwickelt. Die Bildung quartärer Zentren bei der 1, 2‐Arylborierung erfolgt durch Kreuzkupplung eines tertiären organometallischen Komplexes (siehe Schema). Die 1, 1‐Arylborierung wird durch Katalysatoroptimierung ermöglicht und erfolgt über eine Kaskade aus β‐Hydrid‐Eliminierung und Reinsertion.